Molecular Characterization and Expression of Cytochrome P450 Aromatase in Atlantic Croaker Brain: Regulation by Antioxidant Status and Nitric Oxide Synthase During Hypoxia Stress - Rahman, Md Saydur; Thomas, Peter (Frontiers in Physiology, 2021)
We have previously shown that nitric oxide synthase (NOS, an enzyme) is significantly increased during hypoxic stress in Atlantic croaker brains and modulated by an antioxidant (AOX). However, the influence of NOS and AOX on cytochrome P450 aromatase (AROM, CYP19a1, an enzyme) activity on vertebrate brains during hypoxic stress is largely unknown. In this study, we characterized brain AROM (bAROM, CYP19a1b) cDNA in croaker and examined the interactive effects of hypoxia and a NOS-inhibitor or AOX on AROM activity. The amino acid sequence of croaker bAROM cDNA is highly homologous (76-80%) to other marine teleost bAROM cDNAs. Both real-time PCR and Northern blot analyses showed that bAROM transcript (size: 2.8 kb) is highly expressed in the preoptic-anterior hypothalamus (POAH). Hypoxia exposure (dissolved oxygen 1.7 mg/L for 4 weeks) caused significantly decreases in hypothalamic AROM activity, bAROM mRNA and protein expressions. Hypothalamic AROM activity and mRNA levels were also decreased by pharmacological treatment with N-ethylmaleimide (NEM, an alkylating drug which modifies sulfhydryl groups) of fish exposed to normoxic conditions. On the other hand, treatments with Nω-nitro-L-arginine methyl ester (NAME, a competitive NOS-inhibitor) or vitamin-E (Vit-E, a powerful AOX) prevented the downregulation of hypothalamic AROM activity and mRNA levels in hypoxic fish. Moreover, NAME and Vit-E treatments also restored gonadal growth in hypoxic fish. Double-labeled immunohistochemistry results showed that AROM and NOS proteins are co-expressed with NADPH oxidase (generates superoxide anion) in the POAH. Collectively, these results suggest that the hypoxia-induced downregulation of AROM activity in teleost brains is influenced by neuronal NOS activity and AOX status. The present study provides, to the best of our knowledge, the first evidence of restoration of AROM levels in vertebrate brains by a competitive NOS-inhibitor and potent AOX during hypoxic stress.